TINGKAT PENERAPAN PENDEKATAN SAINTIFIK ANTARA BUKU AJAR EDUPARK FISIKA MIFAN WATERPARK PADANG PANJANG DENGAN BUKU STANDAR - Trisma, Elsi; Hamdi, Hamdi; Sari, Dewi Puspa (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
The scientific approach is a learning process that is procedurally designed according to the general steps of scientific activity. This study aims to determine the suitability of the application of the scientific approach in accordance with the 2013 curriculum for SMA / MA. The research used is descriptive research with a qualitative approach. The population in this study was the Edupark Physics research books. The standard book used is seen from several high school physics textbooks made in Indonesia and used in West Sumatra. The sample in this study was the Edupark Textbook of Mifan Waterpark Padang Panjang Physics and standard books namely Physics book for SMA / MA class X curriculum 2013 revised 2016 and class XI curriculum 2013 in 2017 published by Erlangga with the instruction of Marthen Kanginan. The data in this study were taken using research instruments and data collection techniques through documentation studies. The results showed that the level of appropriateness of the application of the scientific approach in the textbook Edupark Physics Mifan Waterpark Padang Panjang based on Permendikbud No. 103 of 2014, there are still many subject matter that have not applied the steps in the scientific approach, so that the results obtained are not in accordance with the percentage 39.6 %. Whereas the standard book that is used has a percentage of 38.2% with the category not quite right. Thus it can be concluded that the Teaching Edupark Textbook of Mifan Waterpark Padang Panjang has a category that is equivalent to the standard book used. However, it is necessary to conduct a review so that the application of the scientific approach to the two books has more appropriate results.